PENGEMBANGAN APLIKASI MATAKU DUA “MEMAHAMI SURAT AT-TAKATSUR BERSAMA DUBI & AMI” UNTUK PEMBELAJARAN PAI - yanti, Risma Rosma; Oktaviani, Siti Nurkhaliza; Cintyaloka, Aura; Aeni, Ani Nur (PENDIDIKAN SAINS DAN TEKNOLOGI, 2025)
Understanding the Al-Qur'an has a very important role. But often understanding the verses of the Koran, especially those that have deep meaning, is a challenge for students in elementary schools. This research aimed to investigate the potential of elementary school students in improving their understanding of PAI material, especially understanding the short letters of the Al-Qur'an. The research method taken is the DnD method and was developed through the ADDIE model which includes Analysis, Design, Development, Implementation, and Evaluation. This research produced data taken from interviews with SDN Sindang II teachers and students, as well as filling out questionnaires by 24 grade 3 elementary school students. The results of this data can be concluded that the majority of students can understand the material regarding the meaning of the at-takatsur letter through the MATAKU DUA android application "Understanding the Meaning of the At-Takatsur Letter with Dubi and Ami" and learning can run effectively and improve students' thinking abilities.